Ethics of Public Administration - Machmud, Fikri Eka Aji; Denok Kurniasih; Tobirin Tobirin (HM Publisher, 2024)
One factor that significantly influences how well companies and public administration players carry out their operations is ethics. The ethical issues that arose, including nepotism, collusion, and corruption, made the implementation of public administration ethics in the Indonesian government bureaucracy crucial. The qualitative technique was employed in this study, with primary data coming from observations and secondary data coming from media and literary analysis. The public emphasized and criticized public bureaucracy throughout the reform era because, according to studies, a small number of Indonesian government officials lack responsibility in carrying out their powers, duties, and obligations. In addition to enforcing the law, the government must develop and apply public administration ethics for its bureaucratic machinery in order to tackle this issue.